(untitled) (Journal of actual problems of jurisprudence, 2020)
In the article on the basis of recent years statistical data given research of the structure, condition and general dynamics of property crimes in our country and in neighboring countries – the Russian Federation and the Kyrgyz Republic, with an emphasis on home thefts. In recent years the level of thefts is stably high and the crime rate is largely determined by the share of thefts of another’s property in it. High rates of researched type of crime are due to large-scale changes in almost all segments – political, economic, social. The economic crisis caused by the pandemic of the coronavirus COVID-19 is gaining momentum everywhere, which drastically reduces the level of population welfare, while alcoholism, drug addiction, and certainly unemployment have increased. At the same time high degree of public danger of these crimes should be noted, which makes the fight against them one of the priority areas of 37 М.Е. Берлыбекова activity of the internal affairs bodies. According to statistics the total number of recorded criminal offenses in our country and in the Kyrgyz Republic has increased, while in the neighboring Russian Federation it is at approximately the same level with slight fluctuations. At the same time our country is “leading” in crimes against property. In average in Kazakhstan share of criminal offenses against property from the total number of criminal offenses is 80%, in the Russian Federation – 57%, in the Kyrgyz Republic – 41%. This means that with significantly larger number of recorded crimes in Russia than in our country, the number of crimes against property from the total number of crimes is lower than similar crimes in Kazakhstan. The share of thefts from the total number of criminal offenses against property is in average 69% in the Russian Federation and in our country it is in average 75%. In the Kyrgyz Republic, more than one third of all crimes are crimes against property (in average 41%), among them almost the entire number accounted for thefts (in average 89%), which is significantly higher in Russia and Kazakhstan. It is clear that thefts are characterized by high rates regardless the fluctuations in the level of the total number of recorded crimes. Kazakhstan, having a smaller area in comparison with Russia, is ahead of it in terms of these indicators, which shows the necessity for effective measures aimed to improving the situation. Key words: offenses, crime, state, theft, prevention.